Pengaruh Karakteristik Individu, Karakteristik Pekerjaan, dan Karakteristik Organisasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bantul Yogyakarta - Yati Suhartini (Universitas PGRI Yogyakarta, 2022)
The goal of this study is to find out how the individual characteristic, job characteristic,organizational characteristic toward employee job satisfaction in Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bantul. This study is a quantitative approach. Populations of this reseach are all employee in Dinas Tenaga Kerja dan Transmigrasi Bantul, totally 61 respondent. Technique of data collection is conducted by questionnaire and analyzed by using a variety of linear regressions.This analysis's findings indicate that the individual characteristic value of the regression coefficient is 0,407 and significant 0,008 (<0,05). The job characterictic has a significant and positive impact on job satisfaction with regression coefficient value is 0,312 and significant 0,036 (<0,05). The organizational characteristic has a positive and significant effect on job satisfaction with regression coeffisient value is 0,443 and significant 0,022 (<0,05). Test-F shows that individual characteristic, job characteristic, organizational characteristic significant effect on job saticfaction, evidenced by result test F 28.483 and significant Test F 0,000 (<0.05). The adjusted R2 amountto 0,579 which means 57,9 % of job satisfaction are influence by individual characteristic, job characteristic, organizational characteristic.